REFORMA AL CÓDIGO ORGÁNICO INTEGRAL PENAL, PARA INCORPORAR UNA NORMA QUE SANCIONE AL PERITO QUE FALTARE A LA VERDAD EN SU INFORME, Y CAUSAN PERJUICIO pecuniario A LAS PARTES - Valarezo Jaramillo, Luis Eduardo (2015)
The objective of this research is to determine a legal reform Comprehensive Organic Penal Code to incorporate a provision to punish those experts who fail to truth in his report, in order to sharpen sanctions for this type of legal experts, to forewarn the rights that the parties in the process The law as such has the power to punish the offender fail to comply with standards established by these legal bodies, but we must take into consideration that our Comprehensive Organic Penal Code does not provide a penalty for experts who fail to truth in his report, hurting the parties and denied the right to due process, taking into consideration that would be left defenseless persons receiving this benefit by experts and therefore it is important to sharpen sanctions in order to ensure a report without preferences, and always scientifically exposing the truth inside. The research is founded on the need to propose alternatives to ensure a report without margins of error and the ability that these people should have to perform a job of this magnitude, knowing that through their knowledge the experts are not an assistant and advisor within a process, because the judge required in a given trial becoming an expert in a particular subject, as the case being judged. 5 As research work is based on a documentary and field scientific research, descriptive, the art to obtain field information was the survey, whose instrument is the questionnaire was aimed at thirty lawyers free exercise of the city of Loja. The contents of the Conceptual, Doctrinal and legal framework formed the basis for my research. The methodology responded to the development of the following stages: collection of bibliographic material, design and format of the survey interview, applying them, tabulation, analysis and interpretation of results.